Prevalence of pressure injuries and the management of support surfaces (mattresses) in adult intensive care patients: A multicentre point prevalence study in Australia and New Zealand. Issue 1 (January 2021) - Yarad, Elizabeth; O'Connor, Anne; Meyer, Jason; Tinker, Matthew; Knowles, Serena; Li, Yang; Hammond, Naomi E.
Abstract: Background: Pressure injuries (PIs) are a patient safety issue that impact patient outcomes. Intensive care unit (ICU) patients are at high risk of PIs. Objectives: To report the prevalence and classification of documented PIs in adult ICU patients, the use of pressure injury risk assessment tools, and support surface management as a part of the prevention of PIs. Methods: This was a prospective, single-day, multicentre, cross-sectional study of patients aged ≥ 16 years admitted to adult ICUs in Australia and New Zealand (ANZ), August 2016 as part of the Australian and New Zealand Intensive Care Society Clinical Trials Group (ANZICS-CTG) Point Prevalence Program. Findings: Data were collected on 671 patients (58% male) in 47 ICUs. The mean [standard deviation] age and weight were 60.2 years [17.2 years] and 82.1 kg [29.7 kg], respectively, with a severity of illness score (Acute Physiology and Chronic Health Evaluation [APACHE] II) of 18.2 [8.4]. PIs were reported in 10% (70/671) of patients. Patients with a PI had a mean APACHE II score of 22.5 [standard deviation; 7.7], and 57.1% (40/70) met the criteria for sepsis on the study day. There were 107 PIs documented on the study day (N = 107) in the 70 patients with nearly half of PIs present on ICU admission (46.7%; 50/107). The sacrum was the most common location for PIs (28.9%; 31/107) and then the heels (15.9%; 17/107). All units routinely use a risk of PI assessment tool and were cared for on an active or reactive support surface. Patients with a PI were more often moved to an active support surface. Conclusions: The prevalence rate was reported at 10% for PIs for adult intensive care patients on the study day. More than half of the patients with a PI had signs of sepsis on the study day and a higher severity of illness, and more were cared for on active support surfaces. Most PIs were located at the sacrum and then the heels. All clinical sites routinely used a PI risk assessment tool.